Comparison of the quality of the teacher made tests with achievement tests and their influence on the success of pupils: case study - Říčan, Jaroslav; Škoda, Jiří; Hermanová, Viktorie; Lanková, Barbora (Scientia in educatione, 2022)
This article compars achievement tests and so-called “teacher-made” tests. The main objective of this case study is to explore and discrepate the results of pupils’ scorings based on whether is test of the same subject has been matter created by the educator or by the researcher. For this reason, the authors ascertain: (1) the quality of teacher-made tests and achievement tests created by the researchers in relation to the regularities of creating achievement tests and (2) the existence of a connection between pupils’ results within their percentage scoring in teacher-made tests and in achievement tests. In order to meet the objectives, the researchers compiled 5 achievement tests on topics that the pupils had been subjected to in the fourth grade of elementary school, during primary science classes. These were then compared to 5 teacher-made tests made by the educator. The study indicates insufficient qualitative aspects of the teacher-made tests (reliability; the ratio of subjectively and objectively scoreable tasks; the ratio of tasks requiring lower and higher cognitive operations; scoring method). Although the correlation analysis revealed a moderately high correlation between the percentage score of pupils in teacher-made tests and achievement tests, we would rather expect a continuity approaching absolute continuity. The results are discussed in relation to the current paradigm of creating didactic tests. The article also points out the limitations of the study and indicates potential ways of further empirical direction.